Pemanfaatan Teknologi Digital dalam Layanan Konseling: Efektivitas dan Aksesibilitas - Nurhijrah Lathifah Jannah; Julhidayat Muhsam (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study examines the utilization of digital technology in counseling services as a response to the transformation of mental health service demands that require flexibility, efficiency, and broad reach. The research problem focuses on the extent of e-counseling effectiveness, the level of service accessibility for the community, and the key challenges influencing its implementation. The study employs a qualitative approach using a systematic literature review method of 25 reputable scientific articles published between 2015 and 2025. The synthesis results indicate that e-counseling demonstrates a high level of effectiveness, reflected in service flexibility (92%), client openness (88%), cost efficiency (85%), satisfaction level (81%), and intervention success rate (76%), particularly for mild to moderate cases. The accessibility aspect also shows significant achievements, including ease of access (90%), expanded geographical reach (87%), and reduced social stigma (83%), thereby reinforcing the role of e-counseling as an inclusive alternative solution. Nevertheless, implementation still faces several challenges, such as limitations in nonverbal communication, data security risks, digital inequality, and low technological competence among counselors. The findings conclude that e-counseling is a strategic innovation that is both effective and adaptive; however, it requires adequate infrastructure support, improved digital literacy, and appropriate regulatory frameworks to ensure optimal and sustainable implementation. The novelty of this study lies in its integrative approach, which simultaneously examines effectiveness and accessibility alongside the technical, psychological, and structural factors influencing them, resulting in a more comprehensive analytical framework compared to previous studies that tend to be partial.